SARS-CoV-2 infection protects against rechallenge in rhesus macaques - Abishek Chandrashekar; Jinyan Liu; Amanda J. Martinot; Katherine McMahan; Noe B. Mercado; Lauren Peter; Lisa H. Tostanoski; Jingyou Yu; Zoltan Maliga; Michael Nekorchuk; Kathleen Busman‐Sahay; Margaret Terry; et al. (2020)
An understanding of protective immunity to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is critical for vaccine and public health strategies aimed at ending the global coronavirus disease 2019 (COVID-19) pandemic. A key unanswered question is whether infection with SARS-CoV-2 results in protective immunity against reexposure. We developed a rhesus macaque model of SARS-CoV-2 infection and observed that macaques had high viral loads in the upper and lower respiratory tract, humoral and cellular immune responses, and pathologic evidence of viral pneumonia. After the initial viral clearance, animals were rechallenged with SARS-CoV-2 and showed 5 log10 reductions in median viral loads in bronchoalveolar lavage and nasal mucosa compared with after the primary infection. Anamnestic immune responses after rechallenge suggested that protection was mediated by immunologic control. These data show that SARS-CoV-2 infection induced protective immunity against reexposure in nonhuman primates.